Open Borders? Immigration in Open Source Projects - Bird, Christian (Proceedings of the Fourth International Workshop on Mining Software Repositories, 2007)
Open source software is built by teams of volunteers. Each project has a core team of developers, who have the authority to commit changes to the repository; this team is the elite, committed foundation of the project, selected through a meritocratic process from a larger number of people who participate on the mailing list. Most projects carefully regulate admission of outsiders to full developer privileges; some projects even have formal descriptions of this process. Understanding the factors that influence the "who, how and when" of this process is critical, both for the sustainability of FLOSS projects, and for outside stakeholders who want to gain entry and succeed. In this paper we mount a quantitative case study of the process by which people join FLOSS projects, using data mined from the Apache Web server, Postgres, and Python. We develop a theory of open source project joining, and evaluate this theory based on our data.